A practical system for road marking detection and recognition - Wu, Tao; Ranganathan, Ananth (2012 IEEE Intelligent Vehicles Symposium, 2012)
We present a system for detecting and recognizing road markings from video input obtained from an in-car camera. Our system learns feature-based templates of road markings from training data and matches these templates to detected features in the test images during runtime. We use MSER features and perform the template matching in an efficient manner so that our system can detect multiple road markings in a single image. Our system also scales well with the number of categories of road markings to be detected. For evaluating our system, we present an extensive dataset (available from www.ananth.in/RoadMarkingDetection.html) of road markings with ground truth labels, which we hope will be useful as a benchmark dataset for future researchers in this area.